Expert opinion on gray areas in asthma management: A lesson from the innovative project “revolution in asthma” of the Italian thoracic society (AIPO‐ITS) - Adriano Vaghi; Raffaele Antonelli Incalzi; Simona Barbaglia; Maria Beatrice Bilò; Francesco Bini; Mauro Carone; Lorenzo Cecchi; Alfredo Antonio Chetta; Andrea Claudio Comel; Fausto DeMichele; Giuseppe Insalaco; Antonino Musarra; et al. (Clinical and Translational Allergy, 2025)
Abstract Background Despite the availability of numerous guidelines for asthma management, their recommendations are not consistently implemented in clinical practice. This discrepancy between guidelines and real‐world practice among Italian healthcare professionals was explored during the “Revolution in Asthma” training program, which identified “gray areas” and barriers preventing clinicians from adopting guideline‐based approaches. Objective This study aims to analyze the key challenges in asthma management and provide evidence‐based solutions to improve adherence to guidelines in clinical practice. Methods A group of experts from the Scientific Committee of the Revolution in Asthma project reviewed the program's findings, focusing on three main areas of asthma management: diagnosis, control, and treatment. The experts summarized clinicians' main needs and questions for each area and provided evidence‐based responses and practical recommendations. Results The study highlights critical challenges in asthma treatment, addressing two key questions: (a) What are the possible uses and indications for short‐acting β‐agonists in asthma patients? (b) How should asthma treatment be initiated and adjusted based on asthma control? The expert panel developed practical, operational tools to support general practitioners and specialists (pulmonologists and allergists) in optimizing asthma management. Conclusion This paper serves as a knowledge co‐creation initiative, bridging the gap between clinical guidelines and daily practice. By offering concrete recommendations, it aims to enhance the application of guideline‐based asthma management among healthcare professionals.